2020
DOI: 10.1016/j.hlc.2019.05.188
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Versus Antegrade Approach for Coronary Chronic Total Occlusion in an Algorithm-Driven Contemporary Asia-Pacific Multicenter Registry: Comparison of Outcomes

Abstract: Background The use of a retrograde approach and algorithm-driven CTO (chronic total occlusion) percutaneous coronary intervention (PCI) has become widespread, and many registries have reported good results. This study established a new algorithm and applied it to current CTO practice and collected a CTO registry to document the results. It compared the outcomes of a retrograde versus antegrade approach in a contemporary multicentre CTO registry. Methods Between 1 January 2016 and 31 December 2016, consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…The study selection process is described in Figure S1. Twelve observational studies with a total of 10,240 patients (10,363 lesions) met our inclusion criteria 4,8,10–17,24,25 . The characteristics of the included studies are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection process is described in Figure S1. Twelve observational studies with a total of 10,240 patients (10,363 lesions) met our inclusion criteria 4,8,10–17,24,25 . The characteristics of the included studies are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported patients from North America, 4,8,11 four from Europe, 10,12,16,17 and five from Asia 13–15,24,25 . The retrograde approach was used as the primary approach in two studies 17,24 ; after the failure of antegrade approach in two studies 10,16 ; and as a mix of both in the rest of the studies 4,8,11–15,25 . The retrograde arm included 2,789 patients (2,816 lesions), while the antegrade arm included 7,451 patients (7,547 lesions).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with current study, baseline characteristics and comparison between those who underwent retrograde versus antegrade procedures are listed by Wu et al, they found number of stents implanted in CTO vessel was 2.1 in Antegrade versus 2.5 in retrograde with significant difference, p<0.001. on the other hands, their results was similar to our finding regarding procedure time (minutes) which significantly prolonged in retrograde than antegrade. Also, Right coronary artery CTO was more commonly approached with retrograde (58% vs 38.2%) and in-stent restenosis cases were more commonly performed through an antegrade approach only (12.6% vs 5.7%) with significant difference, In addition, Karmpaliotis et al, reported that, the retrograde approach contributed to 28.7% of all technical success at a cost of more contrast (300 versus 245 [180-320] mL; P< 0.001), longer procedure time (183 versus 100 min; P< 0.001), compared with antegrade-only cases, respectively [125,126].…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, refined guidewires, microcatheters, and balloons suitable for the retrograde approach have become available, and the techniques to cross the CTO have matured. [7][8][9][10] Hence, the retrograde approach has gained greater popularity than before, and experienced operators use this technique more liberally as an initial strategy when interventional collaterals are present. 4,5,11 However, the advantages of the retrograde approach as an initial strategy over its use as a rescue strategy have not been studied.…”
Section: Introductionmentioning
confidence: 99%